COMPARATIVE ANALYSIS PRACTICES OF POLITICAL STABILITY IMPLEMENTATION IN SOUTHEAST ASIA - Eliza Meiyani; Delila Putri Sadayi; Fadhil Hayan Mochammad (RADJA PUBLIKA, 2025)
Stability is a condition of a system whose components tend to fall into, or return to, an established relationship. Stability is the same as the absence of fundamental or chaotic changes in a political system, or changes that occur within agreed or predetermined boundaries. Development requires security and stability. The development itself must also include security and stability, even the development of security and stability is carried out together with development in other fields. This study uses descriptive qualitative methods, with data collection techniques in the form of literature studies by looking at previous studies, as well as online news as a supporting source. From the data obtained, it will be processed by linking it with the theories that have been previously designed. The approach to political stability as a form of government resilience can be seen from the government management system related to the economy, social, and state security, thus creating political stability in it. Singapore's government tends to have good governance so that it affects the level of the economy and the stability of the country itself, in contrast to Thailand and Myanmar which have a fluctuating index. Especially Myanmar, which has the smallest index for 10 years below the index of 20. This is influenced by the leadershipofr of the warring parties so that it has an impact on coups that often occur.